Numerical Study of Wall Shear and Velocities Using a Commercial CFD Code: Some Crucial Aspects to Consider (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
This paper presents the numerical prediction of wall shear and velocities in steady and superposed pulsatile turbulent flow in a pipe, the phenomena that can be observed in hydropower. The previously conducted experiment is a base for this study and some crucial aspects of CFD while using a commercial code have been emphasized. The widely-accepted grid convergence index approach is adopted to quantify the discretization uncertainty and the results are validated against the experiment. The influence of the wall functions applied in the code is also studied with two turbulence models: standard k-ε and kω based SST model. The time-averaged results of superposed flow with small amplitude unsteadiness are equivalent to results from the steady flow. The results and the method used in this paper may be useful for the CFD simulations in hydropower applications like penstock and bifurcations designs. HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue: 21, July, 2017Page: 45-49Upload Date: July 20, 2017